1996
DOI: 10.1002/(sici)1097-0215(19960717)67:2<294::aid-ijc23>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen expression, antibody localisation and immunophotodetection of human colon cancer liver metastases in nude mice: A model for radioimmunotherapy

Abstract: 2Division of Nuclear Medicine,Colorectal cancer frequently disseminates through the portal vein into the liver. In this study, outbred Swiss nude mice were adapted to facilitate the induction of liver metastases by a pre-grafting treatment with 6 Gy total body irradiation and i.v.injection of anti-asialo GM I antibody. One day later, cultured LS I74T human colon cancer cells were injected into the surgically exposed spleen, which was resected 3 min later. In 48 of 65 mice, a few to several hundred liver metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The histological analysis of the liver showed that the number and size of the metastases did indeed decrease with time after the injection of the therapeutic dose of 131 I-labeled F33-104, which was not observed after a tracer dose. In accord with the tracer studies, 4,18) the initial radioactivity uptake by the metastases was high and was maintained until day 6, but decreased thereafter. Despite the high radioactivity uptake by the metastases, the clearance of radioactivity from the blood was retarded and slower than that from the metastases.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The histological analysis of the liver showed that the number and size of the metastases did indeed decrease with time after the injection of the therapeutic dose of 131 I-labeled F33-104, which was not observed after a tracer dose. In accord with the tracer studies, 4,18) the initial radioactivity uptake by the metastases was high and was maintained until day 6, but decreased thereafter. Despite the high radioactivity uptake by the metastases, the clearance of radioactivity from the blood was retarded and slower than that from the metastases.…”
Section: Discussionsupporting
confidence: 63%
“…14) Small lesions are thought to possess several properties favorable for RIT; 1) the radioactivity uptake by smaller lesions is higher and more homogeneous than that by larger lesions, [15][16][17][18] 2) the radiation dose necessary to control smaller lesions is expected to be significantly lower than that needed for larger lesions. 19) In the present investigation, the pharmacokinetics of a radiolabeled antibody in RIT were investigated to estimate the dose absorbed by the metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A direct correlation between the accumulation of MAbs in melanoma xenografts and the density of a cell surface melanoma-associated glycoprotein has been reported by Shockley et al (1992b). Similarly, a positive relationship between CEA content in tumor tissue and uptake of anti-CEA MAbs has been observed in vivo (Vogel et al, 1996), although in other studies on anti-CEA MAbs no clear correlation was observed (Blumenthal et al, 1992;Folli et al, 1993).…”
Section: Discussionmentioning
confidence: 67%
“…Cy5-conjugated monoclonal antibodies were used for in vivo tumor location by Folli et al (1994), Vogel et al (1996, and Ballou et al (1994Ballou et al ( , 1995aBallou et al ( ,b, 1996Ballou et al ( , 1997 using both mouse tumor models and human tumors xenografted in nude mice. Cyanineantibody conjugates proved to be both adequately stable and highly visible in vivo.…”
Section: Fluorochrome-labeled Antibody Targetingmentioning
confidence: 99%